2004
DOI: 10.1128/aac.48.3.918-923.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Indinavir and Nelfinavir in Treatment-Naive, Human Immunodeficiency Virus-Infected Subjects

Abstract: AIDS Clinical Trials Group protocol 388 was designed to compare a three-drug regimen (indinavir with dual nucleosides) to a four-drug regimen (indinavir plus nelfinavir or indinavir plus efavirenz with dual nucleosides). Blood samples from patients taking indinavir and nelfinavir were collected over 8 to 12 h following a specified dose and were analyzed with high-performance liquid chromatography. Pharmacokinetic data were derived by using noncompartmental analysis. Following administration of indinavir every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The former value is very similar to that found by DiCenzo et al. [30] in naïve patients treated with indinavir plus 1250 mg nelfinavir twice daily (mean AUC of 33 106 ng ml −1 h and 33 269 ng ml −1 h in two groups of nine and seven patients also receiving either 1000 mg twice daily or 1200 mg twice daily of indinavir, respectively). The mean AUC obtained by van‐Dijke et al.…”
Section: Discussionsupporting
confidence: 89%
“…The former value is very similar to that found by DiCenzo et al. [30] in naïve patients treated with indinavir plus 1250 mg nelfinavir twice daily (mean AUC of 33 106 ng ml −1 h and 33 269 ng ml −1 h in two groups of nine and seven patients also receiving either 1000 mg twice daily or 1200 mg twice daily of indinavir, respectively). The mean AUC obtained by van‐Dijke et al.…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies have reported the halflife of efavirenz after repeated dosing to be approximately 40 to 50 h with no major influence noted when a protease inhibitor is combined (1,5,9). These data also provide new information, in that efavirenz pharmacokinetics were stable over 32 weeks.…”
supporting
confidence: 52%
“…426, 2000). Induction effects of efavirenz on other HIV-1 protease inhibitors have also been described (1,5). In addition, a stable AUC ratio of metabolite to parent was observed in both arms; thus, a possible reduction in oral bioavailability could also contribute to the observed results.…”
mentioning
confidence: 76%
“…Saquinavir and indinavir increase nelfinavir concentrations, whereas nelfinavir has variable effects on indinavir [16,17]. Atazanavir increases saquinavir plasma concentrations, but it is commonly prescribed with low-dose ritonavir [18].…”
Section: Interactions Among Antiretrovirals In Combination Regimensmentioning
confidence: 99%